Evaluating an increased spill regime as a management tool to improve downstream passage of salmon smolt - Hansson, Mattias (Karlstads universitet, Institutionen för miljö- och livsvetenskaper (from 2013), 2022)
The anadromous Atlantic salmon (Salmo salar) is dependent on river connectivity to reach spawning and rearing habitats in rivers. Most rivers are today fragmented by artificial barriers such as hydroelectric powerplants (HEP) which impede this migratory movement. As an effort to mitigate river fragmentation, upstream passages have been built at some impediments, but passage facilitating downstream migration has been commonly disregarded until recently. The increased mortality associated with downstream movement through hydroelectric turbines have caused population declines and extirpation in some areas. A common first measure to improve downstream passage is to increase spill discharge during critical time periods. In this study we aim to evaluate the efficiency of increased spill as a management tool and investigate the effect on environmental and physiological factors on fish passage in River Mörrumsån, Sweden. This was done by tracking salmon smolt using high resolution acoustic telemetry and time-to-event models. The results were then further explored in relation to 2D-hydraulic models of different spill scenarios. The results show that increasing the spill at Upper Hemsjö HEP resulted in a relatively high impediment passage efficiency. Spill gate passage was best explained by the proportion of spill in relation to intake channel discharge and diel period. Increased spill and nights without ambient lights where positively associated with spill gate passage rate. Increased levels of spill seamed to increase the attraction to the spill gate passage zone which could be explained by the increased area of flow directed toward the spill gate observed in the hydraulic model, showing the usefulness of hydraulic models as an additional tool in evaluation and planning of remedial measures. The result in this study shows that increased spill can be an effective way to ameliorate river fragmentation, however this should be put in relation to the goal of the mitigation measure as increased spill only creates a temporary ...